Science as a Tool of Power: Examining Gendered Control in Fay Weldon's The Cloning of Joanna May - Rashmi Devi and Komal Verma (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Fay Weldon's The Cloning of Joanna May explores the intersection of science and gender politics, examining how scientific advancements, specifically cloning, are employed as tools of control and dominance. This paper investigates the patriarchal manipulation embedded in scientific practices within the novel and its implications for gendered power dynamics. By analyzing the portrayal of cloning technology and its role in Joanna May's life, the research sheds light on how science reinforces existing power structures and perpetuates gendered oppression. Through feminist and sociological lenses, the study critiques the ethical boundaries of scientific progress and its cultural repercussions, advocating for a gender-conscious approach to technological innovation. Furthermore, this paper delves into the psychological impacts of cloning on identity and agency, illustrating how the fragmentation of individuality reflects broader societal attempts to compartmentalize and diminish women's autonomy. By juxtaposing the personal narrative of Joanna May with the overarching scientific agenda, the research highlights the dehumanizing consequences of treating individuals as experimental subjects. Ultimately, the study calls for a reimagining of scientific frameworks that prioritize ethical integrity, inclusivity, and an awareness of their socio-political ramifications.